Construction of a specific test for estimating coordination in rhythmic gymnastics - Radaš, J.; Milenkovic, E.; Milcic, L. (Science of Gymnastics Journal, 2022)
Rhythmic gymnastics is a combination of sport and art in which the ability of coordination plays a very important role. Since there are not enough specific tests that would assess coordination, both in the selection of children for potential rhythmic gymnasts, as well as in monitoring the training process, the main purpose of this paper is to construct a coordination assessment test that will be applied specifically to rhythmic gymnastics. The sample consisted of 93 students of the 3rd year of integrated undergraduate and graduate study at the Faculty of Kinesiology, University of Zagreb (average age 21 ± 1 year). In addition to the newly constructed test "Echappe" with the rope (MKEV), three other tests were used: ground maneuverability (MAGONT), the jumping hoop forward (MKOOPO), and the back polygon (MREPOL). Microsoft Excel 365 was used to facilitate data preparation and visualization, while IBM SPSS Statistics 26 was used for statistical analysis, with arithmetic mean and standard deviation as descriptive indicators, Shapiro-Wilks test to determine distribution normality, Kruskal-Wallis test with Bonferroni correction for validation, and Fleiss Kappa for reliability determination, which was further determined by Spearman`s Rank correlation. The results showed that there is no evidence that "Echappe" with the rope measures the coordination required for success in rhythmic gymnastics, and that further research is needed with redefined criteria that will contribute to the improvement of metric characteristics of the test.